The present personal : philosophy and the hidden face of language - Kenaan, Hagi (Columbia University Press, 2005)
Is philosophy deaf to the sound of the personal voice? While philosophy is experienced at admiring, resenting, celebrating, and, at times, renouncing language, philosophers have rarely succeeded in being intimate with it. Hagi Kenaan argues that philosophy's concern with abstract forms of linguistic meaning and the objective, propositional nature of language has obscured the singular human voice. In this strikingly original work Kenaan explores the ethical and philosophical implications of recognizing and responding to the individual presence in language. In pursuing the philosop.